Dyspnoea and restrictive lung disease due to mediastinal and pleural lipomatosis in morbid obesity. Issue 5 (9th April 2019) - Lim, Jen Yuh; McAnulty, Kim A.; Chang, Catherina L.
Abstract : Dyspnoea in obese patients can be multifactorial and complex. Mediastinal and pleural lipomatosis can be associated with obesity and is usually considered asymptomatic and benign. We report an obese 39‐year‐old man who presented with progressive dyspnoea, where in addition to obstructive sleep apnoea and obesity hypoventilation syndrome, was found to have massive mediastinal and pleural lipomatosis causing restrictive lung disease. Pleural lipomatosis are generally slow growing so conservative management is recommended. However, complications such as haemorrhage and compression of adjoining organs can occur in pleural lipomas, so surgical excision can be considered in some instances. Abstract : Exertional dyspnoea in obesity is common and may be due to a number of factors. We report a case of large volume mediastinal and pleural lipomatosis causing significant dyspnoea in an obese individual. This is a rare complication of obesity and should be considered in obese patients when other causes of dyspnoea have been excluded.